Impact of disability on different domains of health-related quality of life in the noninstitutionalized general population - Javier Mar; Isabel Larrañaga; Arantzazu Arrospide; et al (Dove Medical Press, 2010)
Javier Mar1,2, Isabel Larrañaga3, Arantzazu Arrospide1, José María Begiristain31Research Unit, Hospital Alto Deba, Navarra 16, Mondragón, Spain; 2Clinical Management Unit, Hospital Alto Deba, Navarra 16, Mondragón, Spain; 3Gipuzkoa Health Authority, Basque Government, Sancho El Sabio 35, Donostia-San Sebastián, SpainAbstract: The relationship between disability and health related quality of life (HRQL) is complex because of the role that function plays in the measurement, and certain points need to be dealt with in greater detail when the analysis is applied to the different dimensions of HRQL. The purpose of this study was to assess the impact of disability on different domains of quality of life. Variables were drawn from the 2002 Basque Country Health Survey. Logistic regression models were constructed to measure the adjusted effect of disability on quality of life as determined by the SF-36 questionnaire. The models were adjusted for sociodemographic variables and the presence of comorbidity. The greatest difference between disabled and nondisabled subjects was found in the physical components of the questionnaire. Odds Ratios (ORs) for a suboptimal level of quality of life as determined by functional status were much higher for the physical than for the mental dimensions. Adjustment for different variables showed a decrease in ORs in the physical, mental, and social dimensions. This study establishes a significant relationship between disability and the loss of quality of life in both physical and mental dimensions of SF-36, irrespective of the associated disease.Keywords: quality of life, disability, health status, SF-36